Conceptual Issues in DCDD Donor Death Determination - Bernat, James L. (The Hastings Center report, 2018)
Despite the popularity, success, and growth of programs of organ donation after the circulatory determination of death (DCDD), a long-standing controversy persists over whether the organ donor is truly dead at the moment physicians declare death, usually following five minutes of circulatory and respiratory arrest. Advocates of the prevailing death determination standard claim that the donor is dead when declared because of permanent cessation of respiration and circulation. Critics of this standard argue that while the cessation of respiration and circulation may be permanent, it may not be irreversible at the moment death is declared because, if cardiopulmonary resuscitation were performed, it might succeed. And because irreversibility of cessation of respiration and circulation is required by both the statute and the biological concept of death, the donor must be alive. Who is correct? Making two related distinctions clarifies the cause of the disagreement over whether the DCDD donor is dead and points to a possible resolution. First, in a determination of death, there is an important distinction between the permanent and the irreversible cessation of circulation and respiration—two associated phenomena that are often confounded. Second, there is an important distinction between the medical practice standard for death determination, in which physicians certify the permanent cessation of vital functions as sufficient for death declaration, and the underlying biological concept of death that requires the irreversible cessation of vital functions because death, by definition, is an irreversible event.